Bill of Lading Issuance Process in Export of Goods at PT Seroja Jaya Agency Kuala Tanjung Branch - Qhodry Darmawi; Suratni Suratni; Aja Avriana (International Forum of Researchers and Lecturers, 2024)
Bill Of Lading is a document of receipt of goods that have been loaded onto a ship that serves as proof of ownership, and a contract between the carrier and the sender. The export process in the shipping world requires the issuance of a Bill Of Lading as a condition for transporting goods and the obstacle is the exporter's delay in sending the Shipping Instruction document. The purpose of writing this paper is to find out the process of issuing a Bill Of Lading in the export of goods. as well as efforts made so that the export process can run smoothly at PT. Seroja Jaya Agency, Kuala Tanjung Branch. The efforts made so that the process runs smoothly, including the Bill Of Lading must be received directly from the carrier where the Bill Of Lading is issued by the sender, the Bill Of Lading must state the name and shipping address, the Bill of Lading must be signed by the captain, the Bill Of Lading must be matched with the invoice and Letter of Credit, the Bill Of Lading date must not exceed the shipping date, the Bill Of Lading must match the Letter of Credit regarding the implementation of payment.